Wybrane zagadnienia kontroli współdziałania podmiotów publicznych i prywatnych w sferze gospodarki komunalnej - Kiczka, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article offers an analysis of selected legal issues regarding components of a legal structure of control regarding cooperation between public and private entities in municipal services. The text’s subject matter deals with the key categories in contemporary state. The analysis concludes that the subject is adomain of jurisprudence seeing the effectiveness of public property laws as connected especially with the construction of both control and supervision. The analysed topics which are also relevant in the European Union should take into account scientific accomplishments in the field. These legal topics require further analysis by those in public economic law domain.
Keywords: gospodarka komunalna; podmioty publiczne; podmioty prywatne; współdziałanie; kontrola